2.) What value for c will make the expression a perfect square trinomial?x2 – 7x + c

-49/4
-7/2
7/2
49/4

Answers

Answer 1
Answer:

Answer : (49)/(4)

Given expression is x^2 - 7x + c

To make perfect square trinominal we use completing the square method

In completing the square method we add and subtract the half of square of coefficient of middle term

Here coefficient of middle term is -7

Half of -7 is (-7)/(2)

Square of (-7)/(2) is ((-7)/(2))^2 = (49)/(4)

So the expression becomes x^2 - 7x + [tex] (49)/(4) that gives perfect square trinomial

Hence , the value of 'c' is (49)/(4)


Answer 2
Answer:

The value for c will make the expression a perfect square trinomial is 49/4

How to determine the value of c?

The equation is given as:

x^2 - 7x + c

Take the coefficient of x

k = -7

Divide it by 2

k/2 = -7/2

Square both sides

(k/2)^2 = (-7/2)^2

The above represents the value of c.

So, we have:

c = (-7/2)^2

Evaluate

c = 49/4

Hence, the value for c will make the expression a perfect square trinomial is 49/4

Read more about trinomials at:

brainly.com/question/1538726

#SPJ5


Related Questions

Bilquis practices the piano 903 minutes in 3 weeks. Assuming she practices the same amount every week, how many minutes would she practice in 5 weeks?
How much is 200 tens
Morgan is walking her dog on an 8-meter-long leash. She is currently 500 meters from her house, so the maximum and minimum distances that the dog may be from the house can be found using the equation |x – 500| = 8. What are the minimum and maximum distances that Morgan’s dog may be from the house?
The sum of the first 65 odd, positive integers is?I know the answer is 4225, but I don't know how to solve.
If 4x-3=13, then 4x=16

Shana wants to use all 62 feet of the fencing she has to make a rectangular run for her dog. She decides to make the length of the run 20 feet. She writes and solves the equation 2 l plus 2 w equals 62 to find the width of the run.Which statements are true of the solution? Check all that apply.

The value of w is 10 feet.
The value of w can be zero.
The value of w cannot be a negative number.
Substitution is used to replace the variable l with a value of 20.
The subtraction property of equality is used to isolate the term with the variable w.

Answers

Answer:

The value of w cannot be a negative number.

Substitution is used to replace the variable l with a value of 20.

The subtraction property of equality is used to isolate the term with the variable w.

Step-by-step explanation:

Answer:

C,D,E

Step-by-step explanation:

Y = 10
x = 3

x + y + y + 17 + y = ?

Thanks!!

Answers

To answer this we will first substitute for each variable and den solve. lets do it:-

x + y + y + 17 + y = ? 

y = 10

x + 10 + 10 + 17 + 10 =  

x = 3

3 + y + + y + 17 + y = ?

Now lets write it out:-

3 + 10 + 10 + 17 + 10 = ?

Now lets solve step by step:-

3 + 10 = 13 
13 + 10 = 23
23 + 17 = 40
40 + 10 = 50

So, 3 + 10 + 10 + 17 + 10 (x + y + y + 17 + y) =  50

Hope I helped ya!! xD 
Substitute:-3 + 10 + 10 + 17 + 10 =
 
Solve:-3 + 10 + 10 + 17 + 10 = 50

Pleaseeeee helppp!!!!!!!!!!!

Answers

4^(2x)=7^(x-1)\n16^x=7^x\cdot7^(-1)\n(16^x)/(7^x)=(1)/(7)\n\left((16)/(7)\right)^x=(1)/(7)\nx=\log_{\tfrac{16}{7}}(1)/(7)\approx-2.35389

D= 11/5(p-15)

solve for p.

Answers

Answer:  The required solution for p isp=(11+75D)/(5D).

Step-by-step explanation:  We are given to solve the following equation for the unknown variable p :

D=(11)/(5(p-15))~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

To solve the given equation for p, we must find the value of p in terms of D.

From equation (i), we have

D=(11)/(5(p-15))\n\n\n\Rightarrow D=(11)/(5p-75)\n\n\n\Rightarrow D(5p-75)=11\n\n\Rightarrow 5Dp-75D=11\n\n\Rightarrow 5Dp=11+75D\n\n\Rightarrow p=(11+75D)/(5D).

Thus, the required solution for p isp=(11+75D)/(5D).

D=11/5p-33
11/5p=D+33
p=5/11D+15

Which counterexample disproves this statement?
for all integers x, 1/x less than or equal to x

Answers

One counter example would be -2. -1/2 is more than -2.

What is the pattern?6+4= 210
9+2= 711
8+5- 313
5+2= 37
7+6= 113
9+8= 117
10+6= 416
15+3= 1218

Answers

First you need to subtract both numbers and then, add them up. You'll receive e.g. 6-4=2 and 6+4=10, then just type them one after another, which will give you 6+4=210.